2004
DOI: 10.2165/00002512-200421150-00004
|View full text |Cite
|
Sign up to set email alerts
|

Hyperparathyroidism in the Elderly Patient

Abstract: Primary hyperparathyroidism is a common metabolic bone disease and currently presents a significant management dilemma. Most of the patients have few relevant symptoms and surgical parathyroidectomy offers the prospect of cure with freedom from the risk of long-term complications or the need for a follow-up. However, there is a natural reluctance to subject elderly patients to an operation where the balance of advantage is less clear. Advances in parathyroid imaging resulting in a greater use of targeted or fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Although age <50 years is one of the criteria for surgery indicated by the guidelines for asymptomatic PHPT [9, 19], owing to the natural history of disease in this age group [19], to date only a few studies have evaluated the effect of age on the clinical presentation of PHPT [7, 8, 20, 21]. Some studies of the clinical features of juvenile PHPT have been recently reported [20, 21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although age <50 years is one of the criteria for surgery indicated by the guidelines for asymptomatic PHPT [9, 19], owing to the natural history of disease in this age group [19], to date only a few studies have evaluated the effect of age on the clinical presentation of PHPT [7, 8, 20, 21]. Some studies of the clinical features of juvenile PHPT have been recently reported [20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…Few data are available regarding the influence of aging on the clinical presentation of PHPT, in particular its effect on disease management for patients >65 years ( i.e., older adults) [7, 8]. We, thus, evaluated a large unselected series of sporadic PHPT, assessing the clinical features and the likelihood of meeting the surgical criteria recommended by current guidelines for older adults compared with younger adults.…”
mentioning
confidence: 99%